2023
DOI: 10.3390/nano13020272
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived CeO2 and CeZrOx Solid Solutions: Exploring Ce Reduction through FTIR and NEXAFS Spectroscopy

Abstract: The development of Ce-based materials is directly dependent on the catalyst surface defects, which is caused by the calcination steps required to increase structural stability. At the same time, the evaluation of cerium’s redox properties under reaction conditions is of increasing relevant importance. The synthesis of Ce-UiO-66 and CeZr-UiO-66 and their subsequent calcination are presented here as a simple and inexpensive approach for achieving homogeneous and stable CeO2 and CeZrOx nanocrystals. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…These results confirmed that Ce 3+ /CO 2 interaction occurred even on a methoxide-rich CeO 2 surface since formation of b ′-OCH 3 did not oxidize Ce 3+ species. Additionally, the agreement between XPS and Ce 3+ 2 F 5/2 → 2 F 7/2 IR transition confirmed that the latter could be used to qualitatively monitor the cerium oxidation state during reactions as we recently showed . FLP allowed then the parallel presence of polarized 1.21′ carbonates and b ′-OCH 3 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These results confirmed that Ce 3+ /CO 2 interaction occurred even on a methoxide-rich CeO 2 surface since formation of b ′-OCH 3 did not oxidize Ce 3+ species. Additionally, the agreement between XPS and Ce 3+ 2 F 5/2 → 2 F 7/2 IR transition confirmed that the latter could be used to qualitatively monitor the cerium oxidation state during reactions as we recently showed . FLP allowed then the parallel presence of polarized 1.21′ carbonates and b ′-OCH 3 .…”
Section: Resultssupporting
confidence: 78%
“…Additionally, the agreement between XPS and Ce 3+ 2 F 5/2 → 2 F 7/2 IR transition confirmed that the latter could be used to qualitatively monitor the cerium oxidation state during reactions as we recently showed. 62 FLP allowed then the parallel presence of polarized 1.21′ carbonates and b′-OCH 3 . The former possesses a more electrophilic carbon, while the latter is characterized by a highly polarized oxygen, overall resulting in an improved MMC formation (Figure 6).…”
Section: Ch 3 Oh and Comentioning
confidence: 99%
“…The mechanism of surface adsorption and dissociation of hydrogen has been unraveled by DFT calculations, clarifying the Ce reduction pathway and predicting the role of Cu, but it was not possible to experimentally assess the role of a dopant via the identification of the oxidation state and its variations during hydrogen exposure . Soft X-ray absorption spectroscopy (XAS) in ambient pressure conditions has proven to be a powerful method to identify the modifications of the active sites in the real catalyst during operation. …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the Ce K-edge XANES spectrum is comparable to that of CeO 2 (cubic symmetry) with the edge position shifted to lower energy (Figure S3b), highlighting the presence of Ce 3+ as already observed by UV–vis spectroscopy (Figure a). During H 2 activation, Ce K-edge XANES spectra (Figure b) presented a clear evolution analyzed by the multivariate curve resolution–alternating least squares (MCR–ALS) routine, highlighting an increase in the V O concentration through Ce 4+ reduction to Ce 3+ from 63 to 47% (Figure c). ,, Moreover, the fitting of Ce K-edge FT-EXAFS spectra collected during H 2 activation indicates a peculiar behavior of the Ce–O coordination number (CN, Figure c). Indeed, in the range of 25–300 °C CN increases from 6.3 to 8.0 while XANES analysis (see Fraction of Ce Species, Figure c) showed no variation in the Ce oxidation state.…”
mentioning
confidence: 96%
“…When describing ZrO 2 solid solutions, a typical example is CeO 2 −ZrO 2 mixtures, which are well-known catalysts and widely employed because of their oxygen storage capacity and oxygen vacancy content. 11,23,24 The catalyst properties are very sensitive to the material local structure, which can be divided into three main cases: (i) a long-order domain type (i.e., CeO 2 and ZrO 2 are not well mixed, forming nanoaggregates of different dimensions interacting only at their interface -mixed clusters, Figure 1), (ii) a short-order domain type (i.e., CeO 2 and ZrO 2 are mixed at long range, but a part remains unmixed at short range -local clustering, Figure 1) and (iii) an ideal solid solution (i.e., CeO 2 and ZrO 2 are perfectly mixed at the local scale -solid solution, Figure 1). 25 With the aim of locating Zn/Ga-ZrO 2 catalysts within these categories, we used a commercial CeZrO 4 as a benchmark catalyst with a Ce:Zr ratio of 1:1 for our characterization strategy (Supporting Information (SI), Table S1).…”
mentioning
confidence: 99%